Implementation of Digital Marketing Strategy with Chatbot Technology - Ramadhan, Farhan Fathur; Sitanggang, Andri Sahata; Wibawa, Julian Chandra; Radliya, Nizar Rabbi (International Journal of Artificial Intelligence Research, 2023)
Chatbots are a rapidly growing technology in the field of digital marketing. They are computer programs designed to simulate conversation with human users. Chatbots can be integrated into websites, mobile apps, and messaging platforms to provide instant customer service and support, as well as personalized recommendations and promotions. By using natural language processing (NLP) and machine learning (ML) techniques, chatbots can understand and respond to user input in a human-like manner. They can also be programmed to respond to specific keywords, trigger events, and customer behavior. Chatbot implementation in digital marketing can help companies to improve customer engagement, increase sales and reduce costs. However, the key to successful chatbot implementation is to ensure that the chatbot is designed to meet the specific needs of the target audience and that it is integrated into the overall marketing strategy. This thesis explains the beneficial role of chatbots and shows how chatbots can be integrated into digital marketing strategies.